Les langues de la diffusion scientifique : une question pour les géographes et les géographies - Nathalie Lemarchand; Antoine Le Blanc (EchoGéo)
In July 2014, the CNFG (French National Committee for Geographers) organized a two-day forum to discuss the relationship between languages, social contexts of scientific production, and the overtly admitted language of scientific exchange, that is, English. It invited all French-speaking geographers, from different "national" and "linguistic" contexts, but also all geographers and geographies interested in sharing their views and experience on the diffusion and production of knowledge in the global context. Indeed, globalization affects both the production and diffusion of scientific knowledge in all regions of the World, where English has become the de facto lingua franca of science. As it is the case in many countries, French geographers are more than ever under pressure to publish in English, and so are their scientific journals. This is often talked about as a fatality or else, as a necessity, in order to make one's work known in world geographic circles. But is there something lost in translation? More importantly, is there something lost in the production of scientific work in the social sciences within a single global language? Those questions go far beyond the simple question of the decline of French as an international language; it raises crucial interrogations such as the normalizing process of "scientific English" in the social sciences, the input of diversity in the global science, the disqualification of "local" case studies, etc. At this Forum, many countries were represented (Belgium, Canada, UK, Germany, Russia ...), which expressed a diverse International experience. The IGU President Vladimir Kolosov and Dieter Soyez of the UGI Executive Board participated. Four round tables were organized: Globalization of knowledge; Global science and the local; Knowledge dissemination; Academic Formation. The account of the Forum and the ideas and proposals that came out of it have been presented at the Congress of the IGU in Krakow in August 2014. The final report will be published in an International journal.